Fenomena Pasar Tradisiaonal Rao, Pasaman - Septrian Rahim, Idra; Deni, Deni; A, Hendra (Rifa'Institute, 2023)
The market is a collection of traders and buyers who meet each other, interact, link each other and create nominal goods or prices in the market. This rao traditional market is also known by people outside of the rao sub-district and even people from the Penyabungan area (North Sumatra) also take the time to come to sell and buy in this market. This market is very crowded especially on Saturdays, because Saturday is a weekday at the market. The rao traditional market is not only known for that, it is also known for providing complete needs for the community. This market is open every day from 06:00 WIB to 18:00 WIB, various types of merchandise that the community needs are in this market, ranging from clothing to food needs available in this market, in a market that certainly has a variety of activities and of course must have a complex space so that activities in the market can run smoothly. This market still has a close bond with the community, the closeness can be seen by traders and buyers who look very familiar, like relatives and even like family.This research aims to find out the attachment of people and places based on experience and explore the phenomena that occur in traditional markets. The method used is a descriptive qualitative method by identifying with interviews, observations. The research uses David Seamon's theory of Phenomenological Perspectives on Place, Lifeworld, and Live Emplacement, the elements examined in the research are Place, Lifeworld and Home.The results of the analysis show that in Rao traditional markets that make them still very much needed by the community because they are able to understand and provide what is needed by customers or the community, the most important thing where in traditional markets prices can be negotiated and have family values. That way people become interested in coming back to the market.